Political Dynasties: Threats or Contributions to Democracy - Raihan Naufal; Muhammad Ramadhan; Muhibban (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
The purpose of this research is to explore the role of political dynasties in democracy and their impact on the stability and quality of the democratization process. The method used includes a comprehensive literature review of various case studies and theories related to political dynasties. The results show that political dynasties can threaten democracy by strengthening oligarchies, inhibiting healthy political participation, and encouraging corruption and nepotism. However, political dynasties can also make positive contributions by offering sustainable political stability, facilitating the transfer of political knowledge, and effectively representing local interests. The conclusion of this study is that the role of political dynasties in democracy is highly dependent on context and certain factors. This journal also provides policy recommendations to minimize the negative risks while harnessing the positive potential of political dynasties in the democratization process